Thermohydraulic characteristics of co/counter swirl flow through a round tube fitted with helical screw tape and twisted tape - Eiamsa-Ard, S.; Yongsiri, K.; Nanan, K.; Thianpong, C. (My University, 2013)
Influence of co/counter swirl flow on the characteristics of friction, heat transfer and thermal performance factor in heat exchanger tubes has been experimentally investigated. Each twisted tape is inserted into a helical screw tape and then these combined tapes are subsequently equipped in a heat exchanger tube for generating the swirl flow. The combined tapes are arranged in two different forms, namely (i) co-swirl arrangement in which their twist are in the same direction and (ii) counter-swirl arrangement in which their twists directions are in the opposite directions. The experiments using helical tapes alone are also performed for assessment. The helical screw tapes are used at three different tape-twist ratios (PR = p/D = 1.0, 1.5 and 2.0), each with three different tape-width ratios (WR = w/D = 0.15, 0.2 and 0.25), while twisted tapes are used at three different twist ratios (YR = y/W = 3, 4 and 5). The results show the maximum thermal performance factor of 1.49 for helical tape alone with PR=2.0 and WR=0.2. At similar conditions, the heat transfer rate associated with the combined tapes in counter-swirl arrangement is 3.4% and 10% higher than those in co-swirl arrangement and helical tape alone.
Keywords: Co/counter swirl flow; Heat transfer enhancement; Helical screw tape; Swirl flow; Thermohydraulic characteristics; Twisted tape